Involvement of Caveolin in Low K(+)-induced Endocytic Degradation of Cell-surface Human Ether-a-go-go-related Gene (hERG) Channels - Massaeli, Hamid (American Society for Biochemistry and Molecular Biology, 2010)
Reduction in the rapidly activating delayed rectifier K(+) channel current (I(Kr)) due to either mutations in the human ether-a-go-go-related gene (hERG) or drug block causes inherited or drug-induced long QT syndrome. A reduction in extracellular K(+) concentration ([K(+)](o)) exacerbates long QT syndrome. Recently, we demonstrated that lowering [K(+)](o) promotes degradation of I(Kr) in rabbit ventricular myocytes and of the hERG channel stably expressed in HEK 293 cells. In this study, we investigated the degradation pathways of hERG channels under low K(+) conditions. We demonstrate that under low K(+) conditions, mature hERG channels and caveolin-1 (Cav1) displayed a parallel time-dependent reduction. Mature hERG channels coprecipitated with Cav1 in co-immunoprecipitation analysis, and internalized hERG channels colocalized with Cav1 in immunocytochemistry analysis. Overexpression of Cav1 accelerated internalization of mature hERG channels in 0 mm K(+)(o), whereas knockdown of Cav1 impeded this process. In addition, knockdown of dynamin 2 using siRNA transfection significantly impeded hERG internalization and degradation under low K(+)(o) conditions. In cultured neonatal rat ventricular myocytes, knockdown of caveolin-3 significantly impeded low K(+)(o)-induced reduction of I(Kr). Our data indicate that a caveolin-dependent endocytic route is involved in low K(+)(o)-induced degradation of mature hERG channels.